ANALYSIS OF TECHNICAL AND LEVEL OF ENVIRONMENTAL FRIENDLY OF THE KELONG BILIS IN MALANG RAPAT VILLAGE GUNUNG KIJANG DISTRICT BINTAN REGENCY RIAU ISLANDS PROVINCE. - Twenty M Sinaga; Pareng Rengi; Arthur Brown (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
Abstract This research is done to know technical aspect that is general construction, operation technique, catch and also environmental friendliness of kelong bilis fishing gear. This research was conducted in April 2018 in Malang Rapat Village Gunung Kijang District Bintan Regency Riau Islands Province. Kelong bilis is a passive fishing gear and is operated at night by using lamp light as a fish pulling factor and usually operated by two fishermen only. Kelong Bilis fishing gear has a size of 12x11 meters and the mesh size is 10x9 meters made of black nylon (Polypropylene) and meshsize 0.1 mm. Kelong Bilis's main catch is Anchovy (Stolephorus sp) and Kelong Bilis’s by catch are Cumi cumi (Loligo sp) and Tamban (Spratelloides delicatulus). Based on the results of the research and the results of interviews conducted on 20 respondents using a weighting system of 9 criteria of environmentally friendly fishing gear according to FAO (1995), kelong bilis fishing gear is a very environmentally friendly fishing gear with score 31.7.Keywords: Technical Analysis, Environment Friendly Level, Kelong bilistechnical aspect that is general construction, operation technique, catch and also environmental friendliness of kelong bilis fishing gear. This research was conducted in April 2018 in Malang Rapat Village Gunung Kijang District Bintan Regency Riau Islands Province. Kelong bilis is a passive fishing gear and is operated at night by using lamp light as a fish pulling factor and usually operated by two fishermen only. Kelong Bilis fishing gear has a size of 12x11 meters and the mesh size is 10x9 meters made of black nylon (Polypropylene) and meshsize 0.1 mm. Kelong Bilis's main catch is Anchovy (Stolephorus sp) and Kelong Bilis’s by catch are Cumi cumi (Loligo sp) and Tamban (Spratelloides delicatulus). Based on the results of the research and the results of interviews conducted on 20 respondents using a weighting system of 9 criteria of environmentally friendly fishing gear according to FAO (1995), kelong bilis fishing gear is a very environmentally friendly fishing gear with score 31.7.Keywords: Technical Analysis, Environment Friendly Level, Kelong bilis